2015
DOI: 10.1136/jnnp-2015-311305
|View full text |Cite
|
Sign up to set email alerts
|

Non-neural phenotype of spinal and bulbar muscular atrophy: results from a large cohort of Italian patients

Abstract: ObjectiveTo carry out a deep characterisation of the main androgen-responsive tissues involved in spinal and bulbar muscular atrophy (SBMA).Methods73 consecutive Italian patients underwent a full clinical protocol including biochemical and hormonal analyses, genitourinary examination, bone metabolism and densitometry, cardiological evaluation and muscle pathology.ResultsCreatine kinase levels were slightly to markedly elevated in almost all cases (68 of the 73; 94%). 30 (41%) patients had fasting glucose above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 53 publications
2
75
0
6
Order By: Relevance
“…As such, altered energy utilization by skeletal muscle may play a part in the systemic manifestations of disease. Recent studies have demonstrated elevated fasting glucose as well as increased total cholesterol, low-density lipoprotein cholesterol and triglyceride levels in a cohort of SBMA patients (Querin et al, 2015). These findings add to a growing appreciation of non-neuronal phenotypes in this disorder, and raise the possibility that targeting metabolic alterations may alleviate disease manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…As such, altered energy utilization by skeletal muscle may play a part in the systemic manifestations of disease. Recent studies have demonstrated elevated fasting glucose as well as increased total cholesterol, low-density lipoprotein cholesterol and triglyceride levels in a cohort of SBMA patients (Querin et al, 2015). These findings add to a growing appreciation of non-neuronal phenotypes in this disorder, and raise the possibility that targeting metabolic alterations may alleviate disease manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, urological involvement has been described: almost 40% of the patients may present moderate signs and symptoms of lower urinary tract obstruction in absence of prostatic hypertrophy, with some of them needing an indwelling bladder catheter [30]. The precise mechanism is still not clear but it is probably related to androgen insensitivity.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Anyway, the only study considering the presence of Brugada's syndrome in a Caucasian SBMA population did not clearly confirm an increased prevalence [30]. At the same time, the presence of a primary cardiomyopathy has been ruled out [32].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…From a clinical point of view, the disease is characterized by slowly progressive lower motor neurons (LMN) degeneration in brainstem and spinal cord, which is associated with multisystem involvement manifesting as androgen insensitivity, heart rhythm abnormalities, metabolic syndrome and sensory neuropathy [6]. The prevalent clinical features of the disease include wasting of proximal limbs muscles with progressive motor impairment [3], associated with mild bulbar involvement.…”
mentioning
confidence: 99%